THE OBJECT OF PUBLIC CONTROL (SUPERVISION) AS AN ELEMENT OF DEMOCRATIC CIVIL CONTROL - Shopina, I. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The purpose of the article is to define the concept and features of the object of public control (supervision) as an element of democratic civil control. The rationale is given that the emergence of democratic civilian control over the security and defense sector was due to the growth of social responsibility of members of society for the state of affairs in the state, combined with the development of mechanisms for ensuring human and civil rights. Attention is focused on the fact that the activity of public control (supervision) in the security and defense sector is constantly increasing, which makes it possible to predict the achievement of greater order and structure by this type of public activity. The article determines that the understanding of the object of control in domestic legal science traditionally covers three main approaches. According to the first of them, the object is a set of bodies and officials who are entrusted with the obligation to carry out a set of actions related to their openness and the need to report to other entities for which they are controlled. The second approach is associated with the recognition of the object of control of the activities or behavior of certain bodies or officials. The third approach, much broader in content, suggests that the object of control is more abstract categories – public goods. The concept is formulated as an object of public control (supervision) as an element of democratic civil control. The definition is proposed: the object of public control (supervision) is a set of public goods of a non-patronage nature, arising from the activity of members of civil society and consisting in the protection of the rights, freedoms and interests of individuals and legal entities, reducing the level of corruption risks and the effective rational use of budgetary funds in the security sector and defense. The article substantiates that the non-patronage nature of public control (supervision) means that the source of benefits is not the state, but civil society. The argument is given that public control (supervision) extends to the protection of the rights, freedoms and interests of not only civilians, but military personnel. The article determines that the subject of public control (supervision) is that part of the object that can be of a specific nature and can be analyzed, measured, compared, etc.